International teacher education promising pedagogies (part A) - Orland-Barak, Lily; Craig, Cheryl J. (Advances in research on teaching ;, 2014)
To this point in time, teacher education has been approached in mostly insular ways because it is largely driven by state and national education policies. However, the spread of the global economy and the increased stature of international comparison tests (i.e., TIMSS) has changed all that. All countries in the world understand that education is vital to human and economic prosperity and that teacher education unavoidably is implicated. But the snag is this: political forces shaping public opinion in individual nations (particularly the U.S.) are deeply divided concerning how teacher education should proceed. This book acknowledges this Achilles heel tension, but does not become weighed down by it. Instead, it focuses on 'the practical' (Schwab, 1969), matters that have been locally deliberated and enacted. Pedagogies are named, origins (cultural/practical/theoretical/policy roots) are traced and a live example of the pedagogy unfurling in the local setting is presented from an insider-view. After that, the conditions necessary for the pedagogy to be transported successfully to another international location are discussed.